Generalized effective medium theory for elastic systems with correlated disorder - Escobar Agudelo, Jorge Mario [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This work develops a generalized coherent potential approximation (CPA) framework to study rigidity transitions in elastic systems with correlated disorder, inspired by the mechanical properties of soft colloidal gels. By extending traditional effective medium theories, we incorporate spatial correlations into the probability distribution of disorder, enabling the analysis of more complex systems. The framework is implemented numerically using a triangular lattice as a test case, leveraging symmetries and approximations to simplify the self-consistency constraint. Our primary contribution is the formulation of a versatile theoretical tool capable of describing rigidity transitions in a wide range of disordered systems, including those with correlated disorder. As a demonstration, we apply the framework to a model inspired by colloidal gels, revealing that spatial correlations shift the critical parameter p_c for rigidity transitions but do not alter the coordination number z at which rigidity occurs, consistent with Maxwell's criterion (z_c=2d). Additionally, we observe scale invariance in the system, indicating universal behavior near the critical transition. These results validate the robustness of the generalized CPA and highlight its potential for studying complex materials such as granular networks, biological tissues, and mechanical metamaterials.

Este trabalho desenvolve uma generalização da coherent potential approximation (CPA) para estudar transições de rigidez em sistemas elásticos com desordem correlacionada, inspirado nas propriedades mecânicas de géis coloidais macios. Ao estender as teorias de meio efetivo tradicionais, incorporamos correlações espaciais na distribuição de probabilidade da desordem, permitindo a análise de sistemas mais complexos. A estrutura é implementada numericamente utilizando uma rede triangular como caso de teste, aproveitando simetrias e aproximações para simplificar a condição de autocoerência. Nossa principal contribuição é a formulação de uma ferramenta teórica versátil capaz de descrever transições de rigidez em uma ampla variedade de sistemas desordenados, incluindo aqueles com desordem correlacionada. Como demonstração, aplicamos a estrutura a um modelo inspirado em géis coloidais, revelando que as correlações espaciais deslocam o parâmetro crítico pc para as transições de rigidez, mas não alteram o número de coordenação z no qual a rigidez ocorre, consistente com o critério de Maxwell (zc = 2d). Além disso, observamos invariância de escala no sistema, indicando comportamento universal próximo à transição crítica. Esses resultados validam a robustez da CPA generalizada e destacam seu potencial para estudar materiais complexos, como redes granulares, tecidos biológicos e metamateriais mecânicos
Teoria generalizada do meio efetivo para sistemas elásticos com desordem correlacionada
Keywords: Matéria condensada macia; Transformações de fase (Física estatística); Fenômenos críticos (Física); Correlação (Estatística); Elastic solids